Hubungan Interdialytic Weight Gain dengan Kram Otot Pada Pasien Hemodialisis di RSU. Royal Prima Medan - Lumbantobing, Krismayanti; Futri, Andina Amelia; Damanik, Mei Indah Suci; Hasty, Alvi Syahri; Harahap, Yunita; Nababan, Tiarnida (Universitas Malahayati, 2024)
ABSTRACT This study aims to evaluate the relationship between interdialytic weight gain and the incidence of muscle cramps during hemodialysis. The method used was a quantitative method with a cross-sectional study design. The research sample consisted of 30 patients undergoing routine hemodialysis in one hospital with a sampling technique, namely total sampling. Data collected included interdialytic weight gain and the incidence of muscle cramps during hemodialysis. The results of the chi-square test analysis showed that there was a significant correlation between increasing body weight and the incidence of muscle cramps during hemodialysis where the p-value obtained was 0.004 (p<0.05). These findings suggest that increased interdialytic weight gain may be a risk factor associated with the occurrence of muscle cramps during hemodialysis. Evaluation in this study requires a hospital policy to provide guidance on preventing excessive weight gain which can be an effective strategy in reducing the incidence of muscle cramps during hemodialysis. Keywords: IDWG, Muscle Cramps Hemodialysis ABSTRAK Riset ini bertujuan mengevaluasi korelasi antar interdialytic weight gain dengan kejadian kram otot selama hemodialisis. Metode yang digunakan adalah metode kuantitaf menggunakan model cross-sectional study, Sampel riset meliputi 30 pasien yang menjalani hemodialisis rutin dalam satu rumah sakit menggunakan pendekatan penghimpunan databerupa total sampling. Data yang dikumpulkan meliputi interdialytic weight gain dan kejadian kram otot selama hemodialisa. Luaran analisa uji chi-squaremenginterpretasikan adanya korelasi antar peningkatan berat badan dengan kejadian kram otot selama hemodialisis secara signifikandimanaskor p-value yang didapatkan yaitu 0,004 (p<0,05). Temuan ini menunjukkan jikanaiknya interdialytic weight gain dapat menjadi agen risiko yang berkaitan terhadap terjadinya kram otot selama hemodialisis. Evaluasi dalam penelitian ini diperlukan adanya kebijakan rumah sakit untuk memberikan bimbingan tentang pencegahan peningkatan berat badan yang berlebihan dapat menjadi strategi yang efektif untuk meminimalisir kejadian kram otot selama hemodialisis. Kata Kunci: IDWG, Kram Otot, Hemodialisis